Tecendo memórias: resistência e luta das operárias da fábrica Santa Cecília (Fortaleza, 1998-1993) - Araújo, Jormana Maria Pereira (2013)
This study examines the experience of women textile workers in the Santa Cecilia factory in the city of Fortaleza (Ceara, Brazil) between 1988-1993 and how issues of migration, domestic work and urban life shaped thier experience as workers. Drawing on thier memories I explore the muliple demensions of the female world of work based on notions of trust and solidarity within a broader structure of social segregation experienced within the working class communities and the city, where they lived and worked. Their experience, shaped by high levels of employment in the textile industry spurred by the transfer of large sectors of the textile industry to Ceara. Specifically factory life at Santa Cecilia was shaped by harsh working conditions, the deadening routine and ever demanding productive process which in turn caused large scale illness and mutilation among women workers. Focusing on the harsh working condition this study explores the processes of resistence and the struggles for basic rights within the larger context of expanding trade union activity and the incorporation of specific female demands and political activity in daily life. Methodolgically, this study is based on the social history of labor and intertwines a variety of sources, such as interviews, photographs, labor union, and legal documents, proccedings from UNITEXTIL, data bases, census data from IBGE and academic studies.